2018
DOI: 10.3390/ijerph15102230
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Level of Self-Regulation and Mindfulness Training on Coping Strategies Used by University Students

Abstract: The purpose of this research was to verify, in a group of psychology students, whether mindfulness training in conjunction with the individual’s level of self-regulation behavior would produce a change in the use of coping strategies. A total of 38 students participated in this study, with one experimental group and one control group, in a randomized controlled trial. Observation of the experimental group revealed a significant decrease in specific emotion-focused, negative coping strategies (preparing for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 43 publications
2
13
1
1
Order By: Relevance
“…Coping strategies: Short Spanish version of the Coping Strategies of Stress Scale (EEC-short) [ 97 ]. The original instrument [ 98 ] consists of a 90-item self-report scale that evaluates 7 basic coping styles: problem-solving coping, negative self-focused coping, positive reappraisal, overt emotional expression, avoidance, social support seeking, and religious coping.…”
Section: Methodsmentioning
confidence: 99%
“…Coping strategies: Short Spanish version of the Coping Strategies of Stress Scale (EEC-short) [ 97 ]. The original instrument [ 98 ] consists of a 90-item self-report scale that evaluates 7 basic coping styles: problem-solving coping, negative self-focused coping, positive reappraisal, overt emotional expression, avoidance, social support seeking, and religious coping.…”
Section: Methodsmentioning
confidence: 99%
“…A growing number of applications and theories have shown that mindfulness training has a positive impact on participants, including positive thinking, emotions, and behaviors. Some examples are the positive effects on perceived stress [41], students’ physical aggression [42], and self-regulation [43]. In the field of theoretical research, many new creative theories are based on Langerian mindfulness theory.…”
Section: Discussionmentioning
confidence: 99%
“…For example, its role in the behavior of students’ motivational-affective variables has been evidenced (de la Fuente et al, 2017b). Also, its mediating role on the effects of Mindfulness Program has been reported (de la Fuente et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%